2019
DOI: 10.1002/suco.201900324
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanical and thermal properties of nano SiO2/hydrophobic silica aerogel co‐doped concrete with thermal insulation properties

Abstract: Lightweight concretes with thermal insulation properties and good compressive strength can be produced by the replacement of normal aggregate of cement mixture with low‐density materials. In this study, sand in a cement mixture has been replaced totally with silica aerogel powder as well as replacement of cement with fly ash. Furthermore, nano silica and silica‐fume were added and incorporated into the concrete matrix. The most obvious finding to emerge from this study was that a lighter sample with no sand co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…To this end, the nanomaterials addition may play a key role in improving the nanostructure of SCC which ultimately leads to enhancement of physical, mechanical, and durability properties of SCC and its sustainability. Regarding this last aspect, the benefits of clean nanotechnology adoption in concrete 20–23 and cement 24–28 production are widely reported, and may indeed lead to a new generation of high‐performance concrete material for sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the nanomaterials addition may play a key role in improving the nanostructure of SCC which ultimately leads to enhancement of physical, mechanical, and durability properties of SCC and its sustainability. Regarding this last aspect, the benefits of clean nanotechnology adoption in concrete 20–23 and cement 24–28 production are widely reported, and may indeed lead to a new generation of high‐performance concrete material for sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
“…This should, accordingly, lead to good mechanical performance and reduced absorbability of the composite [ 89 ]. The work of Al Zaidi et al exemplifies such a solution [ 72 ]. In their study on structural concrete, the authors worked on the improvement of the interface between the silica aerogel and cement matrix.…”
Section: Composition Mechanical and Insulating Properties Of Cementit...mentioning
confidence: 99%
“…This outcome was confirmed via microscope imagery. Final measurements showed that samples with 60% of silica aerogel had compression strength from 27 MPa to 30 MPa, flexural strength of 3.82 MPa and thermal conductivity ranging from 0.86 W/(m·K) to 1 W/(m·K) [ 72 ]. In another experiment, Rostami et al [ 85 ] applied a special treatment to the aggregate.…”
Section: Composition Mechanical and Insulating Properties Of Cementit...mentioning
confidence: 99%
“…Different types of porous or lightweight aggregates have varying effects on the thermal characteristics of resultant concrete. Hence, it is imperative to know about aggregates' thermal properties to enhance the thermal performance of concrete 16 . Various lightweight concretes were invented by replacing whole or portion of sand or gravel with lightweight natural or artificial aggregates to improve the thermal performance of concrete 17–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Fire resistance property at higher temperatures is also studied on these (less dense) concretes and was associated with more resistance to fire 23 . For years, several inventions have been carried out for measuring the thermal conductivity of concrete 16,24 . The techniques for measuring thermal characteristics adopted previously included steady‐state measurement techniques, transient /dynamic measurement technique, and so forth.…”
Section: Introductionmentioning
confidence: 99%